The double movement in Africa: a Nkrumah-Polanyi analysis of free market fatigue in Ghana’s private sector - Langan, Mark (Review of International Political Economy, 2021)
Karl Polanyi’s double movement is a key tool for conceptualising free market fatigue in African business communities wrought by the insecurities of trade liberalisation. Synthesising Polanyi with Kwame Nkrumah’s work on neo-colonialism, the article argues that exhausted business communities in Africa can contest free market reforms and push for a return to developmentalist strategies, underscoring a double movement. In this discussion it highlights Ghana, a ‘donor darling’ in terms of historical implementation of free market reform. It builds upon the author’s engagement with 66 interviewees – business people and policy stakeholders – in relation to the condition of that country’s poultry and tomato industries. Unpacking interviewee narratives, the article points to a striking common theme, namely that business stakeholders call for the re-embedding of the economy via developmentalist strategies to move beyond neo-colonial trade systems. In this vein, the article provides an original contribution to studies of International Political Economy by demonstrating the efficacy of a Nkrumah-Polanyi ensemble for making sense of business communities’ potential role in countermovements for developmentalism in Africa.
Political Science
Keywords: Ghana; Nkrumah; Polanyi; double movement; free trade; neo-colonialism; private sector

Market society and the institutional theory of Karl Polanyi - Cangiani, Michele (Institutional Economics: Perspectives and Methods in Pursuit of a Better World, 2021)
This chapter examines Polanyi’s institutional theory of market-capitalist society. It shows that market society is, according to Polanyi, a peculiarly “economic” society: its economy appears both autonomous and dominant, constraining the structure and evolution of other social subsystems. The chapter also demonstrates that Polanyi’s theory and method allow an explanation of the institutional transformations of market society. In the face of today’s great economic difficulties, social uneasiness, and ecological distress, Polanyian institutionalism remains a rich source of insight on humanity’s challenges and possibilities.

Institutional Economics: Perspectives and Methods in Pursuit of a Better World - Whalen, Charles J. (Routledge, 2021)
Institutional economics is a sociocultural discipline and policy science which draws on the idea that economies are best understood through an appreciation of history, real-world institutions, and socioeconomic interrelations. This book brings together leading institutionalists to examine the tradition’s most essential perspectives and methods. The contributors to the book draw on a broad range of institutional thought from the classic work of Thorstein Veblen, John R. Commons, and Karl Polanyi, to the newer viewpoints of post-Keynesian institutionalism, feminist institutionalism, and environmental institutionalism. Methods range from frameworks used to analyze public policy and institutional change, to modes of analysis including myth busting, historically grounded narratives, and computer-based simulations. Each chapter surveys the origins, development, key features, applications, and frontiers of a particular viewpoint, framework, or mode of analysis. Due consideration is given to both strengths and weaknesses; and woven into the chapters is attention to core institutionalist concepts, including technology, institutions, culture, and complexity. The book provides economists with promising starting points for new research, students with contributions refreshingly in touch with the real world, and policymakers and social scientists with compelling reasons for engaging further with the institutionalist tradition.
Economics
Keywords: economic history; economic theory; institutional economics

Neoliberal Capitalism and Visegrád Countermovements - Hann, Chris; Scheiring, Gábor (Europe-Asia Studies, 2021)
Area Studies; Anthropology
Keywords: countermovement; populism; visegrad countries

Seeing like a Socialist: On Socialist Worldviews from Polanyi to Taylor to Now - Grant, John; Dunlop, Mallory (New Political Science, 2021)
In this article we argue that reinvigorating socialist politics requires championing a socialist worldview that goes beyond the critique of capitalism. Neglecting such an outlook leaves socialism tethered to the fortunes of capitalism and inhibits a broader account of its own virtues. We begin by explaining why worldview thinking is appropriate today. Then we examine two underappreciated works by Karl Polanyi (his 1927 lecture “On Freedom”) and Charles Taylor (his 1974 essay “Socialism and Weltanschauung”). Each treats worldview thinking as indispensable and we use them as catalysts for developing a socialist vision. Finally, we bring our insights to bear on the worldview potential of socialist republicanism. We contend that a promising worldview emerges by elaborating the following components: a political anthropology of human possibilities; anti-capitalism, social freedom, and non-domination; socialist civic virtues; and the promise and limits of pluralism.
Publisher: Routledge _eprint: https://doi.org/10.1080/07393148.2021.2002093
Keywords: TAYLOR; Charles; socialism

The Greater Transformation: Digitalization and the Transformative Power of Distributive Forces in Digital Capitalism - Pfeiffer, Sabine (International Critical Thought, 2021)
This article discusses digitalization and its connection with the political economy of transformation. Its point of departure is Karl Polanyi's historical analysis as presented in The Great Transformation. Polanyi analyzed the development of “self-regulating” markets—with transformative and destructive consequences for individuals, nature, and society—and government efforts to contain these consequences. Polanyi's perspective is compared to Marx's theorem of the development of productive forces. Their respective focal points are different but complementary. For Polanyi, the decisive historical and theoretical break (and the cause of the destructive effects) lies in the act of purchasing human labor, whereas for Marx it lies in the act of producing value and in the relations of production as well as the relations of distribution linked to it. Working from this theoretical basis, current developments in digitalization are analyzed not as a further development within productive forces but as a transforming development of distributive forces. Following the logic of The Great Transformation, current developments should thus not be interpreted as a second great transformation but as the augmentation of the first, leading to a “greater” transformation associated with even more destructive potential. This leaves little hope for a smooth transition into any form of post-growth society.
Sociology
Keywords: digital capitalism; digital transformation; distribution; political economy; productive forces

Karl Polanyi, the New Deal and the Green New Deal - Dale, Gareth (Environmental Values, 2021)
In this paper, I present an analysis of those aspects of Karl Polanyi's social and political thought that relate to environmentalism and 'green' politics today. I discuss whether or not he prefigured the degrowth movement, before focusing on his understanding of the New Deal (1933-1939). At the time of writing, the prospect appears likely of a return, at a global scale, of economic slump, mass unemployment and ecological crisis, the background conditions to which Franklin D. Roosevelt's New Deal was responding on the national scale. The paper concludes by drawing lessons from this comparison for possible Green New Deals.
Keywords: Green New Deal; Karl Polanyi; New Deal; degrowth; embeddedness

On Polanyi - Munck, Ronaldo (Area Development and Policy, 2021)
Karl Polanyi provides a rich repertoire of concepts to build a critical understanding of the world of globalization and alternatives to the status quo. In reviewing two recent collections around the work of Polanyi, we show some of the concepts that might be developed in terms of ‘using Polanyi’. This would include his inspired double-movement concept and the way he dealt with non-capitalist societies. Polanyi is as relevant for the so-called developing societies as he is for the advanced industrial societies where he has garnered most attention.
Publisher: Routledge _eprint: https://doi.org/10.1080/23792949.2020.1830708
Keywords: Polanyi; double movement; globalización; globalization; movimiento doble; no capitalista; non-capitalist; Поланьи; глобализация; двойное движение; некапиталистический.; 全球化; 双重运动; 波兰尼; 非资本主义

Karl Polanyi and the Reappraisal of Happiness Economics - Özveren, Eyüp; Gürpinar, Erkan; Karagöz, Ufuk (Journal of Economic Issues, 2021)
Happiness economics unearths the undesirable effects of economic growth and criticizes the economic model based on the belief in the supremacy of market relations over the relational bonds of society. Economic growth brings about substantial increases in material well-being; yet, it has the potential to destroy the social and environmental fabric of society. This is visible in the post-World War II cross-country variability of the subjective well-being measures, which shows the importance of relational goods and associational activities. These themes echo Karl Polanyi’s concerns over the destructive effects of the self-regulating market mechanism. In this paper, we demonstrate the relevance of the interdisciplinary work of Polanyi for happiness economics. We argue that Polanyi’s conception of the self-regulating market system comes together with the spread of unhappiness. The treatment of labor as a fictitious commodity is of utmost significance in this respect. No less important is the similar degrading of land, a proxy for environment. Furthermore, the distinction Polanyi maintained between “exploitation” and “cultural degeneration” in assessing the Industrial Revolution is useful for this critique. In essence, Polanyi’s approach is relevant to explain the deterioration of social relations, which is thought to be the ultimate reason behind the happiness paradox.
Economics
Keywords: Karl Polanyi; consumption; happiness; hedonism; self-regulating market system

CAPITALISM, DEMOCRACY, AND SOCIAL THEORY IN KARL POLANYI: AN INTERVIEW WITH GARETH DALE - Santos, Rodrigo Salles Pereira dos; Onto, Gustavo Gomes (Sociologia & Antropologia, 2021)
Resumo Uma introdução à entrevista realizada com Gareth Dale (Brunel University) − economista político e especialista na trajetória e na obra de Karl Polanyi − e a um conjunto de textos inspirados na abordagem polanyiana publicados neste número de S&A. Recupera questões-chave apresentadas na entrevista e na obra de Dale, dando relevo à literatura recente produzida sobre o autor, à contínua e difundida relevância das ideias de Polanyi para a compreensão do capitalismo e da democracia, e a uma leitura crítica e aberta de suas contribuições teóricas. Divulga as contribuições específicas, teóricas e empíricas, de quatro artigos originais que mobilizam ativamente conceitos polanyianos no entendimento da pluralidade dos processos de enraizamento e das dinâmicas do movimento duplo, de mercantilização da terra e do trabalho, e da centralidade da praça de mercado no capitalismo contemporâneo; além dos aportes de um registro de pesquisa e duas resenhas sobre agências e pedagogias econômicas e financeirização da vida cotidiana. An introduction to the interview with Gareth Dale (Brunel University) − a political economist and expert on Karl Polanyi’s life and work − and to a set of papers, inspired by the Polanyian approach, published in the current issue of S&A. The paper highlights key questions presented in the interview and in Dale’s work, with a focus on the recent literature produced about the author, the continuous and widespread relevance of Polanyi’s ideas for the understanding of capitalism and democracy, and a critical and open reading of his theoretical contributions. Next, the paper presents the specific contributions, both theoretical and empirical, of four original papers that actively dip into Polanyian concepts in understanding the plurality of the embeddedness processes and the dynamics of the double movement, the commodification of land and labor, and the centrality of the marketplace in contemporary capitalism; as well as the contributions of a research recording and of two book reviews on economic agencies and pedagogies and the financialization of everyday life.
Sociology; Anthropology
Keywords: DALE; Gareth; Karl Polanyi; capitalism; democracy; market

Platform Power and Regulatory Politics: Polanyi for the 21st Century - Cioffi, John W.; Kenney, Martin; Zysman, John (2021)
The rapid rise, expansion, and growing asymmetric power of online platform firms towards other businesses, labor and even the state itself occurred in a context of minimal regulatory oversight. In many respects, because the existing legal system was handicapped in understanding and regulating the new platform business models. The platform firms undermined traditional industry boundaries and developed surprising synergies by expanding in unexpected ways due to their ability leverage data and computational expertise. The growth of these platforms was accompanied by minimal intervention by state actors until recently, as concerns about the platform firms’ remarkable power has attracted the concern of States globally and the previous regime is giving way to intense debate and increasingly interventionist governmental policies and enforcement actions. We examine several salient aspects of this emerging regulatory and political reaction, and suggest that this represents an attempt to rebalance the positions of social groups in their relationship to the increasingly central platform firms. First, we view the rise of, and recent political responses to, the often-predatory power and manipulative conduct of platform firm in terms of a “Polanyian” double movement in which the destabilizing and destructive effects of unchecked corporate power and market development eventually generates political and regulatory responses to constrain private actions by new economic actors as they threaten the social, political, and economic order. Second, incipient legal changes, most notably the EU’s proposed Digital Markets Act and Digital Services Act, indicate a shift in regulatory emphasis from competition (and antitrust) policy and law, which has proven limited in its capacity to address inherent monopolistic tendencies of platform firms and markets, towards more intensive and encompassing forms of social and economic regulation. Finally, the political dynamics of legal and institutional change open up new possibilities for political economic and societal reordering, but the particular changes will likely vary in character and significance across political jurisdictions, and therefore follow distinctive and possibly divergent developmental trajectories. We hypothesize that the EU may be able to become the first-mover in regulating the powerful multinational platform firms. We recognize that we are at the very beginning of a transformational process that is likely to reorder old and generate new political economic interests, identities, coalitions, and conflicts at the sectoral, national, regional, and international levels.
Keywords: European Union; Platform economy; Polanyi; antitrust; monopoly

Constituting the Political Economy of the Kurds: Social Embeddedness, Hegemony, and Identity - Tekdemir, Omer (Routledge, 2021)
This book examines the development of Kurdish political economy and the emergence of collective Kurdish identity within a historical context through three main periods: the late-Ottoman Empire, the initial Republican Turkey era, and then the post-1990s period. It relates historical developments to the dynamics of Kurdish society, including the anthropological realities of the nineteenth century through the moral economy frame, the evolving nature of nationalism in the early twentieth century and the more recent construction of a modern political Kurdishness by means of radical democracy, and an agonistic pluralism shaped by left-wing populism.
Political Science
Keywords: Kurdistan; Political Science / World / Middle Eastern; embeddedness; ethnic studies; middle eastern studies; regional studies

New Limits of the Neoliberalism: Society and Market - Vidal, Laura; Correa, Eugenia (Journal of Economic Issues, 2021)
Neoliberalism has been able to change the markets and the economy of societies around the world. These transformations are especially important with regards to fictitious commodities: land, labor, and money. However, the 2020 pandemic imposes new limits, when life itself is at risk globally. This work highlights the major neoliberal reforms relating to fictitious commodities, the difficulties of society to resist and create counterweights. The health crisis that has emerged with the COVID-19 pandemic is the result of decades of over-exploitation of nature and human beings. The reforms over fictitious commodities, especially labor, have led to a constant and systematic decline of society. This article is supported by the theoretical legacy of Karl Polanyi and Kari Polanyi Levitt that allows us to consider the most important trends of neoliberal reforms and their main objectives.
Economics
Keywords: fictitious commodities; health crisis; neoliberal counterrevolution; neoliberalism

Non-market institutions and crime in US counties: Hayek v. Polanyi - Zullo, Roland (Review of Social Economy, 2021)
Karl Polanyi’s The great transformation emphasized the importance of non-market institutions for social equity and stability. In that same era, Friedrich Hayek postulated in The road to serfdom that superior economies were market-based and featured minimal government. I compare these worldviews in relation to property and violent crime. Using US county data, change in crime is modeled as a function of economic structure, economic conditions, and demographics. Consistent with Polanyi, the size of the public sector in the economy negatively associates with crime. Within the public sector, education is a critical crime-reducing function, more so than law enforcement. Industry diversity is positively associated with crime, contrary to Hayek. Manufacturing equates with lower crime and the size of the private non-profit sector is unrelated to crime. Overall the results favor Polanyi’s assertion that non-market institutions are necessary to counter the harsh outcomes arising from market economic systems.
Publisher: Routledge _eprint: https://doi.org/10.1080/00346764.2019.1663909
Keywords: H41 (public goods); P17 (capitalism performance); Socialism; Z13 (economic sociology); crime; laissez-faire; non-market institutions; public goods

On the meaning and contemporary significance of fascism in the writings of Karl Polanyi - Millett, Kris (Theory and Society, 2021)
This paper assesses the contribution of Karl Polanyi, a theorist largely ignored in fascism scholarship, toward understanding fascism’s interwar rise and present-day implications. In exploring Polanyi’s work in The Great Transformation and lesser-known and unpublished writings, a sophisticated and largely original conception of fascism emerges, rooted in the idea of ‘anti-individualism’ as its foundational trait. Polanyi accounts for fascism’s philosophical content, ideological plasticity, political function and societal form, intervening in debates over how to define fascism, its ambiguity with the populist far-right, and on its both economically reactionary and socially revolutionary qualities. Polanyi’s analysis suggests an enduring vulnerability on the part of liberal capitalism to fascist currents as (1) a solution to the instability of the market economy (and broader incompatibility between capitalism and democracy) at the systemic level, and (2) to the crisis of the individual subject on a social and moral level. I end by considering how Polanyi’s theory might be applied to locate current neo-fascist movements and elucidate the sociological problems underpinning their existence.
Sociology
Keywords: Anti-individualism; Fascism; Neo-fascism; Polanyi; Totalitarianism; Vitalism

Karl Polanyi: a theorist of mixed economies - Szelényi, Iván; Mihályi, Péter (Theory and Society, 2021)
Karl Polanyi’s scholarship is interpreted in radically different ways. The “hard” reading of Polanyi sees him as a radical socialist; the “soft” reading presents him as a theorist of mixed economy. This article sides with the soft interpretation. It uses Polanyi’s biography to explain his theoretical “elusiveness,” presents a novel interpretation of his three types of economic integration, claiming all economies are “mixed.” While it acknowledges Polanyi as one of the major sources of world system theory, it claims that Polanyi saw not only the dangers, but also the necessity and positive consequences of globalization. Finally, it shows that, in spite of Polanyi’s life-long commitment to the political left, his scholarly work did not offer an apology of socialism. Instead this article uses Polanyi’s theory of economic integration to build a critical political economy of state socialism.
Keywords: capitalism; reciprocity; redistribution; rent-seeking; socialism; world system theory

Our Obsolete Marketing Mentality: George Fisk, Meet Karl Polanyi - Benton, Raymond (Journal of Macromarketing, 2021)
Marketing in general can have greater influence if a new, yet old, perspective on marketing is adopted—something akin to the original orientation of marketing. Adopting George Fisk’s definition of marketing and marrying it with notions derived from the institutional economist Karl Polanyi is proposed. The histories of marketing thought and of institutional economics are reviewed to demonstrate their affinity and similar origins. Fisk’s conceptualization of marketing as societies’ provisioning systems is shown to correspond with Polanyi’s conceptualization of economies as instituted processes, admitting more than the market and the state as ways economies have historically and cross-culturally integrated with society. The obsolete marketing mentality is that marketers, including macromarketers, are overly fixated on the market and ignore or overlook alternatives. The Fisk/Polanyi orientation will attract macromarketers interested in marketing and development, critical marketing, sustainability, alternative economies, and those interested in the long-term prospects of macromarketing. Adopting this old, but new, framework will connect the past with the future, permit macromarketers make a mark on a larger intellectual landscape and serve to invite scholars in this larger landscape to engage with macromarketing.
Publisher: SAGE Publications Inc
Keywords: Future of Macromarketing; George Fisk; German Historical School; History of Economic Thought; Institutional Economics; Karl Polanyi; Marketing and Economics; history of marketing thought; macromarketing

Going public with Polanyi in the era of Trump * - Burawoy, Michael (The Routledge International Handbook of Public Sociology, 2021)
After considering different possible elements of the ‘Trump era,’ I will turn to The Great Transformation to periodize capitalism into three waves of marketization and their counter-movements. In the first wave, we follow the commodification of land, money and especially labor, so-called fictitious commodities, and the local counter-movements marketization inspired, reaching to the level of the state. In the second wave, the focus turns on the way marketization generated a reaction from states, seeking to regulate commodification – in other words, processes of de-commodification. Given the tension between capitalism and democracy, in Polanyi’s view essentially two forms of regulation were possible: either democracy suppresses capitalism and we get socialism, or capitalism suppresses democracy and we get fascism. He neither paid much attention to the popular forces that led in either direction nor to the possibility of a compromise between capitalism and democracy that reigned in three decades after World War Two. Beginning in the 1970s, we witnessed the beginning of a third wave of marketization – more commonly known as neoliberalism – that Polanyi did not anticipate. I attribute his failure to anticipate another wave of marketization to the contradictory pressures of accumulation that are temporarily alleviated by commodification. In this third wave, I show how democracy is discredited, and consensus politics dissolves into polarizing movements within and beyond parliamentary politics. The lived experience driving these movements, I argue, revolves around processes of re-commodification and ex-commodification of nature, money, labor and knowledge. This is the terrain upon which sociology must engage its publics. I highlight two approaches, both founded on an organic public sociology that engages directly with publics. On the one hand, there is the empathic public sociology that wades into communities in order to comprehend the distinctive ‘deep narrative’ of right wing populism, typified by Arlie Hochschild’s Strangers in Their Own Land. On the other hand, there is the affirmative public sociology that creates a collective vision based on a dialogue with the practitioners of real utopias, typified by Erik Wright’s How to Be an Anti-Capitalist in the Twenty-First Century.
Sociology
Keywords: Trumpism; marketization; public sociology

Competition in transitional processes: Polanyi & Schumpeter - Hager, Theresa; Heck, Ines; Rath, Johanna (ICAE Working Paper Series, 2021)
We examine parallels and differences in the analyses of societal transition by Karl Polanyi and Joseph A. Schumpeter. We argue that although their understanding of historical processes differs - transformational-political vs. evolutionary-natural - the central mechanism of change they describe is the same. We identify three spheres essential to both authors' works: the economic, the political and the socio-cultural sphere. Polanyi and Schumpeter describe an expansion of the economic sphere culminating in a subordination of the other parts of society. In capitalism this dominance stems from capitalism's emergence as well as the concept of competition. The consequence is a profound change in societal relations. Changes in the socio-cultural sphere in turn produce changes in the political sphere that bring about detrimental consequences for democracy. In our paper we carve out the similarities as well as the differences in the respective theories, clarify the role competition plays therein and discuss the consequences for the political process. We adopt an analytical framework that puts the nearly analogous mechanism of change in the centre. This in turn enables us to make use of the complementarity and to gain valuable insights on the interdependence of capitalism and democracy that can inform trends and phenomena that are currently observed.
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; competition; interdependence

Fascism and the enduring problem of the liberal individual in Polanyi - Millett, Kris (Dewey Studies, 2021)
This application of Polanyi to the question of fascism’s resurgence provides an important corrective to mainstream liberal explanations (e.g., Albright 2018), inviting the reader to “look up rather than down” (Lim 2021) by tying fascism’s significance to the functioning of the capitalist system rather than to the personalities of fascist politicians or their degree of mass support. The merits of this notwithstanding, I argue that current Polanyian treatments have neglected to engage with a core aspect of Polanyi’s theory, which is that fascism, at its roots, is a fundamentally anti-individualist ideology that aims to address a moral and social crisis of the individual subject in liberal capitalism. Omitting this risks obfuscating what makes fascism distinctive as well as why its ideas have retained their appeal.
Sociology
Keywords: essence of fascism; fascism; individualism